A SISTEM PENDETEKSI SUHU RUANGAN: SISTEM PENDETEKSI SUHU RUANGAN DENGAN MENGUNAKAN ARDUINO - Afira, Riandana; Purnama, Ayu Widya; Putra, Teri Ade; Wisky, Irzal Arief (Politeknik Ganesha Medan, 2022)
In this era, all agencies, be it companies, offices, and industries, take advantage of technological developments with computerized systems. This progress gives an important role in human life. Currently, computers are not only used to process data, they can even be used to control an electronics-based system, such as in the field of controlling external equipment, controlling robots, electronic equipment, and so on. Along with the development of these technologies, the authors try to develop a type of electronic component, namely the LM35DZ Temperature Sensor and Arduino. This research was conducted to create a system that can measure temperature in a room using Arduino and the LM35DZ temperature sensor as the main components. This LM35DZ temperature sensor functions to convert the temperature scale into an electrical quantity in the form of a voltage with a high level of precision but is very simple. Arduino functions as a central place for processing all data and instructions, so that it can facilitate the development of a microcontroller application, starting from writing source programs, complications, uploading complication results and testing serial terminals. The use of Arduino in this tool is combined with ATMEGA 328 and the source program used is the C programming language.